Consumers' motivational drivers status consumption and life satisfaction: a case of smartphones among the Generation Y cohort in South Africa - Sithole, Titus Mutsanya (My University, 2019)
One important motivating force that influences a wide range of consumer behaviour is the desire to gain status or social prestige from the acquisition and consumption of goods. More often than not, individuals purchase expensive and luxury goods to display their social standing. In addition, individuals purchase status products to fulfill their material desires and reinforce their group identity. This is often a case with regards to youth consumers who often purchase expensive, luxury smart-phone brands to portray status and impress their peers. This behaviour seems to be trending among student communities. This study sought to investigate the consumers’ motivations for status consumption and life satisfaction for smartphone consumption in Generation Y. This study made use of a non-probability convenience sample. A self-administered questionnaire was designed, based on the scales used in previous studies. A sample of 250 students was chosen to collect the data. A series scale check analysis was made to test the reliability and validity of measures using Statistical Package for the Social Sciences (SPSS) version 25. Also, structural equation modelling (SEM) analysed the hypothesised relationships using Amos version 25 software. The main findings of the study are that materialism has a significant influence on life satisfaction with a path coefficient value for hypothesis 1 is 0.371, which is an indication of a strong association and relationship between materialism and status consumption. Uniqueness has a positive and a significant influence on status consumption with a path coefficient value of 0.034 and the p-value of 0.847. Consumer ethnocentrism has a positive and a significant influence on status consumption with path coefficient value of 0.122 and the p-value of 0.176. Modern status orientations have a significant influence on status consumption with a path coefficient value of 0.717. Finally, status consumption has a significant influence on life satisfaction with a path coefficient value for hypothesis 5 is 0.719, which is an indication of a strong association and relationship between status consumption and life satisfaction. The insights gained from this study will help marketers to better understand youth consumers in their engagement in status consumption, and life satisfaction, which, will ultimately assist the marketing practitioners’ efforts in such a way as to appeal to this segment in an appropriate manner.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce
Keywords: Consumer behavior--South Africa; Generation Y--South Africa; Cell phones--Social aspects--South Africa